Human Behavior Understanding 5th International Workshop, HBU 2014, Zurich, Switzerland, September 12, 2014. Proceedings - Park, Hyun Soo.; Salah, Albert Ali.; Lee, Yong Jae.; Morency, Louis-Philippe.; Sheikh, Yaser; Cucchiara, Rita.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the proceedings of the 5th International Workshop on Human Behavior Understanding, HBU 2014, held in Zurich, Switzerland, in September 2014. The 9 full papers presented in this volume were carefully reviewed and selected from 18 submissions. They are organized in topical sections named: social signals; face and affect; motion analysis; and multiparty interactions.
Social Signals -- How Do You Like Your Virtual Agent?: Human-Agent Interaction Experience through Nonverbal Features and Personality Traits -- Human Involvement in E-Coaching: Effects on Effectiveness, Perceived Influence and Trust -- Just the Way You Chat: Linking Personality, Style and Recognizability in Chats -- Face and Affect -- A New Multi-modal Dataset for Human Affect Analysis -- The Role of Color and Contrast in Facial Age Estimation -- Motion Analysis -- Dominant Motion Analysis in Regular and Irregular Crowd Scenes -- Coupling Fall Detection and Tracking in Omnidirectional Cameras -- Multiparty Interactions -- Learning Sparse Prototypes for Crowd Perception via Ensemble Coding Mechanisms -- Dyadic Interaction Detection from Pose and Flow.
Keywords: Computer science; User interfaces (Computer systems).; Artificial intelligence; Pattern recognition; Computer Science; Pattern Recognition; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Electronic books